Heidegger’s πóλεμοσ - Sodeika, Tomas (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English]This article deals with the problem of the relationship between Martin Heidegger’s philosophy and Daseinanalysis – a trend of psychotherapy that was founded by Medard Boss in Switzerland in the mid-twentieth century. It is generally believed that, in collaboration with Boss, Heidegger was looking for ways in which his developed theory could be applied in practice. The article questions this view and suggests that the seminars, which were held by Heidegger in Boss’s house in Zollikon, were important to Heidegger as a situation, in which during the confrontation between the philosophical and psychotherapeutic discourses occurs the Heraclitean πόλεμος – a tension in which a person may experience the openness of presence.
Keywords: Martin Heidegger; Medard Boss; Daseinanalysis; θεωρία; πόλεμος; being